Detecting women : gender and the Hollywood detective film - Gates, Philippa, 1973- (State University of New York Press, 2011)
In this extensive and authoritative study of more than three hundred films, Philippa Gates explores the "woman detective" figure from her pre-cinematic origins in nineteenth-century detective fiction through her many incarnations throughout the history of Hollywood cinema. Through the lens of theories of gender, genre, and stardom and engaging with the critical concepts of performativity, masquerade, and feminism, Detecting Women analyzes constructions of the female investigator in the detective genre and focuses on the evolution of her representation from 1929 to today. While a popular assumption is that images of women have become increasingly positive over this period, Gates argues that the most progressive and feminist models of the female detective exist in mainstream film's more peripheral products, such as 1930s B pictures and 1970s blaxploitation films. Offering revisions and new insights into peripheral forms of mainstream film, Gates explores this space that allows a fantasy of resolution of social anxieties about crime and, more interestingly, gender, in the twentieth and early twenty-first centuries. The author's innovative, engaging, and capacious approach to this important figure within feminist film history breaks new ground in the fields of gender and film studies. -- From the Back Cover